PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN TRANSAKSIONAL TERHADAP KINERJA PEGAWAI MELALUI PENYELESAIAN KONFLIK - Imam Mahmud Yeni; Mei Indrawati; Soenarmi Soenarmi (CV. ALIM'SPUBLISHING, 2023)
The purpose of this study is to describe and analyze the Influence of Transformational and Transactional Leadership on Employee Performance through Conflict Resolution. This type of research is explanatory research with a quantitative approach. The population is all Pesen Village Government employees 39 people. The sampling technique is by census sampling, so that the sample is 39 people. Methods of data collection with questionnaires and documentation were analyzed using Partial Least Square (PLS). The results showed that transformational leadership, transactional, conflict resolution and the performance of Pesen Village Government employees, Kanor District, Bojonegoro Regency were in the very high category, Transformational leadership had a significant effect on conflict resolution, Transactional leadership had no significant effect on conflict resolution, Transformational leadership had a significant effect on performance, Leadership transactional has no significant effect on performance, conflict resolution has a significant effect on performance, transformational leadership has a significant effect on performance through conflict resolution, transactional leadership has no significant effect on performance through conflict resolution.